State Taxation and the Reallocation of Business Activity: Evidence from Establishment-Level Data - Giroud, Xavier; Rauh, Joshua (Journal of Political Economy, 2019)
Using census microdata on multistate firms and their organizational forms, we estimate the impact of state taxes on business activity. For C corporations, employment and the number of establishments have short-run corporate tax elasticities of −0.4 to −0.5 and do not vary with changes in personal tax rates. Pass-through entity activities show tax elasticities of −0.2 to −0.4 with respect to personal tax rates and are invariant with respect to corporate tax rates. Capital shows similar patterns. Reallocation of productive resources to other states drives around half the effect. The responses are strongest for firms in tradable and footloose industries.